2022
DOI: 10.1080/09506608.2022.2026863
|View full text |Cite
|
Sign up to set email alerts
|

Review on developments of bulk functionally graded composite materials

Abstract: Monolithic components are often insufficient when a combination of conflicting properties, or a variation in properties at different regions within a material is required. Functionally graded composite materials (FGCM) are a relatively new class of materials with a systematic variation of the composition, microstructure, and properties along one direction. The graded structure offers tailorable property combinations not achievable with monolithic composites and significant recent research has been carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 301 publications
0
7
0
Order By: Relevance
“…Amongst these reviews highlighted above, trends in reported challenges and areas of opportunity have emerged. The area of focus here will be on the following two general challenges that remain in adoption of ceramic AM; Limited mechanical strength due to either: low density, processing defects (e.g., interlayer delamination), and/or material composition limitations in existing well‐developed feedstock 1,3,4,16,27,38,49,56,65,67–69,71,72,74,75,79,90,94,112,123,128,145 156 Poor identification and quantification of defects and limited standardization and speed of advancements the processes (feedstock development, processing parameters, postprocessing steps, etc.…”
Section: Challenges and Opportunities In Ceramic Ammentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst these reviews highlighted above, trends in reported challenges and areas of opportunity have emerged. The area of focus here will be on the following two general challenges that remain in adoption of ceramic AM; Limited mechanical strength due to either: low density, processing defects (e.g., interlayer delamination), and/or material composition limitations in existing well‐developed feedstock 1,3,4,16,27,38,49,56,65,67–69,71,72,74,75,79,90,94,112,123,128,145 156 Poor identification and quantification of defects and limited standardization and speed of advancements the processes (feedstock development, processing parameters, postprocessing steps, etc.…”
Section: Challenges and Opportunities In Ceramic Ammentioning
confidence: 99%
“…Limited mechanical strength due to either: low density, processing defects (e.g., interlayer delamination), and/or material composition limitations in existing well‐developed feedstock 1,3,4,16,27,38,49,56,65,67–69,71,72,74,75,79,90,94,112,123,128,145 156 …”
Section: Challenges and Opportunities In Ceramic Ammentioning
confidence: 99%
See 1 more Smart Citation
“…The use of composite materials has increased drastically in the last few decades. 1,2 These materials are heterogeneous in nature and formed by the combination of reinforcing constituents such as llers, particulates, and bres with matrices. 3,4 Furthermore, they have the ability to replace traditional materials such as metals and alloys by providing high strength and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…FGMs are frequently used where one end of a layer must endure hard conditions, and the other side of the substrate must be linked to the base material that requires protection from these hostile surroundings [9][10][11]. FGM manufacturing methods have evolved over the years, with numerous techniques now employed to create these gradient materials, including centrifugal casting, powder metallurgy, vapor deposition, thermal spray, and additive manufacturing techniques [12][13][14]. Centrifugal casting and powder metallurgy processes, in particular, have proven effective in the fabrication of FGMs with smooth variation in microstructures and/or compositions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%